The Effect of Intradialytic Exercise on Fatigue in Patients Undergoing Hemodialysis: A Literature Review - Jusuf, Herlina; Liputo, Gusti Pandi (Babali Nursing Research, 2024)
Introduction: Fatigue is a common and debilitating symptom experienced by patients undergoing hemodialysis. Intradialytic exercise, which involves physical activity performed during dialysis treatment, has been studied as a potential intervention to alleviate this fatigue. This literature review aims to determine the effects of intradialytic exercise on fatigue in patients undergoing hemodialysis. Methods: The literature review search was carried out using three databases, namely Google Scholar, PubMed, and Science Direct. The inclusion criteria for the literature review search were articles with publication years 2019-2024 in Indonesia and English. The articles could be open access. The keywords used in searching for the article were “intradialytic AND fatigue.” Results: The literature review identified fifteen studies for inclusion in the final analysis. Three articles used randomized control trials, seven articles used quasi-experiments, and five articles used pre-experiments. Many types of intradialytic exercises during hemodialysis were discovered. Conclusion: Intradialytic exercises have proven successful in reducing the level of weakness in patients undergoing hemodialysis. Fifteen research articles were found to support the provision of intradialytic exercises to patients undergoing hemodialysis. Intradialytic exercises can include active movement exercises, leg exercises, and relaxation movements.